Factors Associated with Adherence to Antiretroviral Therapy and CD4 Levels among HIV/AIDS Patients - Pibulniyom, Ratnawalee (Journal of Health Science of Thailand, 2017)
This cross-sectional survey was conducted with objectives to 1) characterize demographics factors, adherence to antiretroviral therapy and CD4 levels, and 2) explore associations between demographics and adherence, and between demographics and CD 4 level. Totally 241 HIV/AIDS patients were recruited from out-patient department of Pak Chong Nana hospital. A set of structured questionnaire was administered to collect demographic information and adherence scale and data on CD4 levels were obtained from the NAPHA program. Most of the HIV/AIDS patients were female (57.26%). They disclosed their HIV- serostatus in 40.25 percent. Those with 95 percent of medical adherence accounted for 48.55 percent and those with 30 percent elevated CD4 levels accounted for 53.52 percent. No demographic variable was statistically associated with adherence to antiretroviral therapy or CD4 level. Disclosure of their HIV- serostatus was significantly related to medical adherence and CD4 level (p < 0.01) Health service system should promote skills development for improving adherence to antiretroviral therapy and consider the benefit of HIV status disclosure that should result in medical adherence and elevated CD4 levels in patients.